ANALYSIS OF STUDENTS’ LEARNING DIFFICULTIES FROM PSYCHOLOGICAL FACTORS, LEARNING STRATEGIES, AND LEARNING MANAGEMENT PERSPECTIVES AT ISLAMIC HIGHER EDUCATION - Lenni Marlina Hasibuan; Ismail Harahap; Andi Soloon Harahap; Hamka (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Learning difficulties among higher education students remain a critical issue, particularly in Islamic higher education institutions that integrate academic, moral, and spiritual dimensions. This study aims to analyze students’ learning difficulties from three main perspectives: psychological factors, learning strategies, and learning management at the Institute of Islamic Studies (Institut Agama Islam) Padang Lawas. A qualitative descriptive approach was employed, involving observations, semi-structured interviews, and document analysis. The participants consisted of undergraduate students and lecturers selected through purposive sampling. The findings reveal that students’ learning difficulties are strongly influenced by psychological factors such as low learning motivation, academic anxiety, limited self-confidence, and weak self-regulated learning skills. In addition, the dominance of conventional teaching strategies and limited student-centered learning practices contribute to low engagement and conceptual understanding. From a learning management perspective, constraints related to instructional planning, classroom organization, and evaluation systems further exacerbate students’ learning difficulties. This study highlights the importance of integrating psychologically informed instructional strategies and effective learning management to enhance students’ academic performance in Islamic higher education contexts.